The efficacy of radiation therapy in adrenocortical carcinoma: A propensity score analysis of a population-based study. Issue 17 (April 2017) - Luo, You; Chen, San-San; Zheng, Xiang-Guang; Luo, Li; Wang, Sen
Abstract : Abstract: Adrenocortical carcinoma (ACC) is a rare and malignant tumor. The main treatment is primary surgical resection with or without mitotane therapy. The role of radiation therapy is still controversial. We aim to investigate the survival efficacy of radiotherapy in a large population-based cohort. We queried the Surveillance, Epidemiology, and End Results (SEER) database (1973–2013) to identify cases with ACC. Traditional multivariate Cox regression and propensity score analysis were used to evaluate the effect of radiotherapy on cancer survival. The survival outcomes included overall survival and cancer-specific survival. The treatment effect was evaluated using a hazard ratio (HR) and its 95% confidence interval (95% CI). Five hundred thirty patients diagnosed with ACC were identified. Among them, 74 patients received radiotherapy. In the multivariate Cox regression, radiotherapy did not increase the overall survival (HR 0.794, 95% CI 0.550–1.146, P  = .218) or cancer-specific survival (HR 0.842, 95% CI 0.574–1.236, P  = .388). In the propensity score analysis, the results consistently showed no survival benefit of radiotherapy regardless of the different propensity score analysis methods. Radiotherapy did not improve overall or cancer-specific survival in ACC patients. Further confirmation is needed from multi-institutional prospective studies in the future.